The place of inquiry in mathematics taught within the International Baccalaureate La place de l’enquête en mathématiques enseignées au sein du Baccalauréat International - Lackova, Jana (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract Traditional teaching seems to prevail over problem-solving, and inquiry-based education struggles in finding a stable place in the classrooms. Our research questions the place of inquiry in a particular institutional context that places it in the heart of its educational philosophy, particularly when it becomes an institutionally recognized object, sanctioned by a summative assessment. Keywords: Anthropological theory of didactics, Inquiry, international baccalaureate Résumé L’enseignement traditionnel semble prévaloir sur la résolution de problèmes, et la démarche d’investigation lutte pour trouver une place stable dans les classes. Notre recherche questionne la place de la démarche d’investigation dans un contexte institutionnel particulier qui la place au cœur de sa philosophie éducative, en particulier lorsqu’elle devient un objet institutionnellement reconnu, sanctionné par une évaluation sommative. Mots-clés: Théorie anthropologique de la didactique, enquête, baccalauréat international